2014
DOI: 10.1016/j.socscimed.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of structural stigma and rejection sensitivity on young sexual minority men's daily tobacco and alcohol use

Abstract: Stigma occurs at both individual and structural levels, but existing research tends to examine the effect of individual and structural forms of stigma in isolation, rather than considering potential synergistic effects. To address this gap, our study examined whether stigma at the individual level, namely gay-related rejection sensitivity, interacts with structural stigma to predict substance use among young sexual minority men. Sexual minority (n = 119) participants completed online measures of our constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
183
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(190 citation statements)
references
References 58 publications
6
183
0
1
Order By: Relevance
“…Prospective data from the Growing Up Today Study found that sexual minority youth in the United States living in states with low structural stigma were less likely to report cigarette use in the past year . Furthermore, a recent study on the role of structural stigma on substance use among sexual minority youth found that exposure to structural stigma was significantly associated with daily cigarette use (Pachankis et al, 2014). According to survey selfreport data, LGB youth were more likely to have experienced sexual abuse, parental abuse, assault at school when compared to non-LGB peers (Saewyc et al, 2006;Bontempo and d'Augelli, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Prospective data from the Growing Up Today Study found that sexual minority youth in the United States living in states with low structural stigma were less likely to report cigarette use in the past year . Furthermore, a recent study on the role of structural stigma on substance use among sexual minority youth found that exposure to structural stigma was significantly associated with daily cigarette use (Pachankis et al, 2014). According to survey selfreport data, LGB youth were more likely to have experienced sexual abuse, parental abuse, assault at school when compared to non-LGB peers (Saewyc et al, 2006;Bontempo and d'Augelli, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using diverse methodologies consistently attribute the source of sexual orientation-related mental health and substance use disparities in sexual minorities to disproportionate exposure to minority stress-the stress associated with stigma-related social disadvantage that compounds general life stress. 6,[11][12][13] According to this model, 6 minority stress emerges from stigmatizing societal structures-termed structural stigma 14 -that deny sexual minority individuals (i.e., those who identify as gay, bisexual, or lesbian or engage in same-sex sexual behavior) the same rights and opportunities afforded to heterosexuals. In addition, discrimination within families, religious communities, schools, and workplaces elevate stress and, therefore, the mental health and substance burden experienced by sexual minorities across the lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…LGBT people also experience unique challenges related to discrimination and stigma (Pachankis et al, 2014), victimization (Collier, van Beusekom, Bos, & Sandfort, 2013) 25 and physical abuse (Goldbach et al, 2014;Ignatavicius, 2013) that can negatively affect psychological well-being (see Flentje, Livingston, Roly, & Sorensen, 2015), and for which some persons use substances to help cope Williamson, 2000). It is well established that Q2 30 some of the most powerful institutions in society have historically rejected homosexuality, including various religions, health systems and the media (Meyer, 2013).…”
mentioning
confidence: 99%